Ladies’ Water Aerobics Swim Group - Johnson, Paul (Groupwork, 2014)
Over the course of the past year (2012-2013), the author has been swimming at his local YMCA (Y). Every Monday, Wednesday, and Friday he observed a group of between 10-12 women participating in an aerobics swim group. It gradually dawned on him that this was a recreational, activity support group. What impressed him was the way the women interacted with one another; they were always talking, laughing and clearly enjoying one another’s company. In June of this year, the author decided to approach one of the members of the group and see if she would be willing to share some of her experiences of attending the group. This resulted in her speaking and e-mailing all of the women, who in turn e-mailed and spoke to the author about their reasons for participating in and the benefits they derived from the group. The paper incorporates the narratives of the women regarding the reasons for joining and also the numerous, physical, psychological, emotional, mental health, and social benefits of the group. The author also provides the reader with a number of theoretical concepts from groupwork literature, which further reinforce the numerous benefits of the Ladies’ Aerobic Swim Group.